The State of Police Legitimacy Through the People’s Trust and Satisfaction in the Performance of the Police of Their Duties (American Journal of Multidisciplinary Research and Innovation, 2022)
People are likely to cooperate with the police when they view their authority as legitimate. Police legitimacy is established by the people’s trust in them and the people’s satisfaction in the way they perform their duties. This study surveyed and correlated the community people’s trust and satisfaction in the police’s performance of their duties. There were 2,381 respondents from the different provinces of the Cordillera Administrative Region, Philippines, who participated in the survey. The respondents moderately trust the police and were much satisfied with the way they performed their duties. Age group makes a significant difference in the extent of trust, while gender and age group make a significant difference in the respondents’extent of satisfaction. Pearson’s r (r=.090) shows there is a weak correlation between the trust of the people to the police and their extent of satisfaction on the way the police performed their duties. It is concluded that trust and satisfaction are independent of each other insofar as police legitimacy is concerned. The police should therefore work on improving their image and demonstrating competence inperforming their duties so that the people will cooperate with them and appreciate what they are doing.